The Experience Of Electronic Medical Records Managers In Facing Health System Interoperability Challenges - Surya Utama (STIKES Columbia Asia Medan, 2025)
Interoperability remains one of the most persistent challenges in digital health systems globally, affecting the continuity, quality, and efficiency of care. Electronic Medical Records (EMR) managers are central to implementing and sustaining EMR systems, yet their experiences navigating interoperability challenges are poorly understood. This study aimed to explore the lived experiences of EMR managers and to develop a conceptual understanding of the barriers and coping strategies involved. A qualitative phenomenological approach was employed, guided by van Manen’s interpretive framework. The study involved 21 EMR managers from public and private hospitals across three major healthcare networks. Participants were selected through purposive and snowball sampling, with inclusion criteria requiring at least two years of EMR management experience and involvement in interoperability efforts. Data were collected via in-depth, semi-structured interviews conducted virtually between September and November 2025. Each interview lasted 45–60 minutes, was audio-recorded, transcribed verbatim, and member-checked. Data were analyzed thematically using NVivo 14, following Braun and Clarke’s six-step method. Reflexivity, triangulation, and peer debriefing ensured methodological rigor, in accordance with COREQ and SRQR standards. Four overarching themes emerged: (1) Fragmented Systems, reflecting technical and architectural incompatibilities across platforms; (2) Role Strain and Isolation, describing limited authority and institutional support; (3) Adaptive Workarounds, highlighting informal coping strategies such as manual data tracking; and (4) Systemic Barriers, pointing to policy volatility and vendor resistance. A conceptual “feedback loop of fragmentation” was developed, illustrating how these themes interact to perpetuate interoperability challenges. EMR managers operate as critical yet often overlooked actors in the pursuit of health system interoperability. Supporting their role through policy stability, resource investment, and participatory system design is essential. Future digital health reforms must integrate managerial perspectives to build resilient and connected health information systems.